Determinants of rural household livelihood dependence on non-timber forest products: A case study from Inanda Community, KwaZulu-Natal, South Africa - Wale, Edilegnaw; Nkoana, Mmaphuti Andrias; Mkuna, Eliaza (Frontiers in Forests and Global Change, 2022)
Natural forest resources are the most accessible sources of services, products and incomes for many adjacent rural communities. However, the declining resilience of forests and agricultural sectors particularly in South Africa is concerning and a real public policy challenge. Little is known about the determinants of rural community dependence on natural forests, and the importance of this dependence to rural livelihoods and environmental outcomes. This study investigated factors affecting rural household level of forest dependence and the contribution of natural forests to rural household livelihoods in the ‘KwaZulu-Natal Sandstone Sourveld (KZNSS)’ ecosystem. Employing survey data from 150 forest-dependent households and a logit-transformed Ordinary Least Squares (OLS) model, the study found that there is significant level of forest dependence in the study area. The empirical results indicated that off-farm incomes, employment incomes, forest vouchers received from the ‘Wildlands Project’ pays in exchange for planting trees, values of household assets, changing of time and dates in visiting the forest for the collection of forest products, and perceived changes in temperature significantly influence the contribution of forest resources to rural livelihoods. These results suggested that the exchange economic activities with projects similar to the ‘Wildlands Project’ need to be planned from the start, engaging all the relevant stakeholders, so that it can be embraced by all and the rules understood by all. Furthermore, policy interventions are required to enable rural people meet their livelihoods and diversify alternative income sources to achieve resilience and reduce pressure on natural forests dependence.